Feasibility of chitosan-alginate (Chi-Alg) hydrogel used as scaffold for neural tissue engineering: a pilot study in vitro - Wang, Gan; Wang, Xiaoyan; Huang, Lixiang (Biotechnology, biotechnological equipment, 2017)
In tissue engineering, scaffolding plays an important role in accommodating and stimulating new tissue growth. Chitosan and alginate are two widely used natural polymers in tissue engineering. Here, we prepared the chitosan-alginate (Chi-Alg) hydrogel from naturally derived chitosan and alginate polymers. The Fourier-transformed infrared spectroscopy and X-ray diffraction results demonstrated that a chitosan-alginate hydrogel was constructed due to the strong ionic interaction between the positively charged amino groups of chitosan and the negatively charged carboxyl groups of alginate. The scanning electron microscopy and contact angle results showed the inner porous structure and highly hydrophilic property of chitosan-alginate hydrogel. As the two most promising cell types in nerve tissue engineering, both olfactory ensheathing cells and neural stem cells proliferated well on the chitosan-alginate hydrogel. All results indicated the good potential application of a chitosan-alginate hydrogel for neural tissue engineering.